The Immunological Effect of Oxygen Carriers on Normothermic Ex Vivo Liver Perfusion - Jennings, Heather; Carlson, Kristin N.; Little, Chris; Verhagen, Joshua C.; Nagendran, Jeevan; Liu, Yongjun; Verhoven, Bret; Zeng, Weifeng; McMorrow, Stacey; Chlebeck, Peter; Al-Adra, David P. (Frontiers in Immunology, 2022)
Introduction Normothermic ex vivo liver perfusion (NEVLP) is an organ preservation method that allows liver graft functional assessment prior to transplantation. One key component of normothermic perfusion solution is an oxygen carrier to provide oxygen to the liver to sustain metabolic activities. Oxygen carriers such as red blood cells or hemoglobin-based oxygen carriers have unknown effect on the liver-resident immune cells during NEVLP. In this study, we assessed the effects of different oxygen carriers on the phenotype and function of liver-resident immune cells. Methods Adult Lewis rat livers underwent NEVLP using three different oxygen carriers: human packed red blood cells (pRBC), rat pRBCs, or Oxyglobin (a synthetic hemoglobin-based oxygen carrier). Hourly perfusate samples were collected for downstream analysis and livers were digested to isolate immune cells. The concentration of common cytokines was measured in the perfusate and the immune cells underwent phenotypic characterization with flow cytometry and quantitative reverse transcription polymerase chain reaction (qRT-PCR). The stimulatory function of the liver-resident immune cells were assessed using mixed lymphocyte reactions. Results There were no differences in liver function, liver damage, or histology between the three oxygen carriers. qRT-PCR revealed the gene expression of NF-κB, IL-1β, CCL2, CCL7, and CD14, were significantly upregulated in the human pRBC group compared with naïve, whereas rat pRBC and Oxyglobin groups were not different from naive. Flow cytometry demonstrated the cell surface expression of the immune co-stimulatory protein, CD86, was significantly higher on liver-resident macrophages and plasmacytoid dendritic cells perfused with human pRBC compared to Oxyglobin. Mixed lymphocyte reactions revealed increased allogeneic T cell proliferation in the human and rat pRBC groups compared to the Oxyglobin group. Conclusions Liver-resident immune cells are important mediators of rejection after transplantation. In this study, we show that the oxygen carrier used in NEVLP solutions can affect the phenotype of these liver-resident immune cells. The synthetic hemoglobin-based oxygen carrier, Oxyglobin, showed the least amount of liver-resident immune cell activation and the least amount of allogeneic proliferation, when compared to human or rat pRBCs. To mitigate liver-resident immune cell activation during NEVLP (and subsequent transplantation), Oxyglobin may be an optimal oxygen carrier.